2018
DOI: 10.1021/acs.jpclett.8b00652
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite Carrier Transport: Disentangling the Impacts of Effective Mass and Scattering Time Through Microscopic Optical Detection

Abstract: While carrier mobility is a practical and commonly cited measure of transport, it conflates the effects of two more fundamental material properties: the effective mass and mean scattering time of charge carriers. This Letter describes the correlation of two ultrafast imaging techniques to disentangle the effect of each on carrier transport in lead halide perovskites. Two materials are compared: methylammonium lead tri-iodide (MAPbI) and cesium lead bromide diiodide (CsPbBrI). By correlating photoinduced change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…*DFT calculated reduced mass 𝑚 * =0.14𝑚 0 , experimentally measured reduced mass (for cubic CsPbBrI2) 𝑚 * =0.12𝑚 0 [51].…”
Section: / 30mentioning
confidence: 95%
“…*DFT calculated reduced mass 𝑚 * =0.14𝑚 0 , experimentally measured reduced mass (for cubic CsPbBrI2) 𝑚 * =0.12𝑚 0 [51].…”
Section: / 30mentioning
confidence: 95%
“…Recently, Deng et al revealed that the exciton diffusivities for low-n-valued layered perovskite like BA 2 PbI 4 (n = 1) and BA 2 MAPb 2 I 7 (n = 2) were only 0.06 and 0.07 cm 2 s −1 , respectively, at room temperature [24] which are about one order magnitude smaller than in 3D counterparts (0.54-1.2 cm 2 s −1 ). [25][26][27][28] The corresponding in-plane exciton diffusion lengths were derived to be around 160 nm, which was much smaller than the film thickness (≈400-500 nm) to absorb most of sun light within absorption spectral range. [20,24] Soon Layered perovskites have been employed for various optoelectronic devices including solar cells and light-emitting diodes for improved stability, which need exciton transport along both the in-plane and the out-of-plane directions.…”
Section: Doi: 101002/adma202004080mentioning
confidence: 99%
“…Due to the lowest excitonphonon coupling strength and small out-of-plane distortion in PEA-N1 single crystals among the PEAI layered perovskites family, an impressive exciton diffusivity of 0.648 ± 0.05 cm 2 s −1 is achieved, which is then comparable with that of MAPbI 3 single crystal (0.54-1.2 cm 2 s −1 ). [25][26][27][28] The large in-plane tilting angle in PEA-N1 indicates that the diffusivity could be further improved by mitigating the in-plane distortion. The significantly drop of the diffusivity (75%) from PEA-N1 to PEA-N2 can be attributed to the severe out-of-plane distortion coupled with the increased exciton-phonon coupling strength in PEA-N2.…”
Section: Doi: 101002/adma202004080mentioning
confidence: 99%
See 1 more Smart Citation
“…Information for carrier lifetimes and their contributions to the Voc). Non-radiative recombination decays are accelerated by scatterers that include defects 13 , phonons 50 , impurities 51 and mobile species 52,53 , lowering the Voc. Deep-level defects (that is, those with a thermal activation energy higher than kBT, where kB is the Boltzmann constant) are the predominant trap sources for non-radiative recombination losses, whereas shallow-level defects have a negligible impact on non-radiative decays and Voc 9 .…”
Section: [H2] Defect-assisted Recombination Lossesmentioning
confidence: 99%